Multiple sites and actions of gabapentin-induced relief of ongoing experimental neuropathic pain. Issue 12 (December 2017) - Bannister, Kirsty; Qu, Chaoling; Navratilova, Edita; Oyarzo, Janice; Xie, Jennifer Yanhua; King, Tamara; Dickenson, Anthony H.; Porreca, Frank
Abstract : Abstract: Gabapentin (GBP) is a first-line therapy for neuropathic pain, but its mechanisms and sites of action remain uncertain. We investigated GBP-induced modulation of neuropathic pain following spinal nerve ligation (SNL) in rats. Intravenous or intrathecal GBP reversed evoked mechanical hypersensitivity and produced conditioned place preference (CPP) and dopamine (DA) release in the nucleus accumbens (NAc) selectively in SNL rats. Spinal GBP also significantly inhibited dorsal horn wide-dynamic-range neuronal responses to a range of evoked stimuli in SNL rats. By contrast, GBP microinjected bilaterally into the rostral anterior cingulate cortex (rACC), produced CPP, and elicited NAc DA release selectively in SNL rats but did not reverse tactile allodynia and had marginal effects on wide-dynamic-range neuronal activity. Moreover, blockade of endogenous opioid signaling in the rACC prevented intravenous GBP-induced CPP and NAc DA release but failed to block its inhibition of tactile allodynia. Gabapentin, therefore, can potentially act to produce its pain relieving effects by (a) inhibition of injury-induced spinal neuronal excitability, evoked hypersensitivity, and ongoing pain and (b) selective supraspinal modulation of affective qualities of pain, without alteration of reflexive behaviors. Consistent with previous findings of pain relief from nonopioid analgesics, GBP requires engagement of rACC endogenous opioid circuits and downstream activation of mesolimbic reward circuits reflected in learned pain-motivated behaviors. These findings support the partial separation of sensory and affective dimensions of pain in this experimental model and suggest that modulation of affective–motivational qualities of pain may be the preferential mechanism of GBP's analgesic effects in patients. Abstract : Gabapentin engages endogenous opioid signaling in the anterior cingulate cortex to selectively relieve affective qualities of peripheral nerve injury–induced ongoing pain and in the spinal cord to inhibit nociceptive neuronal excitability and evoked hypersensitivity.